Balancing the stigmatization risks of disability labels against the benefits of special education: Japanese parents' perceptions. (June 2018) - Kayama, Misa; Haight, Wendy
Abstract: Stigmatization can dampen the joys and exacerbate the challenges experienced by parents whose children have disabilities. This qualitative study examines the experiences of eight Japanese parents of their children's mild cognitive and behavioral disabilities and any associated stigmatization at public elementary schools. These parents' perceptions reflected Japanese people's general sensitivity to the threat of stigmatization due to individual differences. During individual interviews, parents described how their sensitivity to others' actual or anticipated negative responses led to social isolation. After significant, sustained efforts to support their children by themselves, most of these parents chose to consult with professionals and secure special education services for their children. They preferred support to be holistically and unobtrusively provided by all school staff members during academic and non-academic activities. The experiences of these Japanese parents underscore the importance of emotional and social support for children with disabilities and their parents. Examination of Japanese parents' perspectives on disability and stigmatization highlights our cultural blind spots, allows us to reflect back on taken for granted beliefs and practices, deepens our understandings, and may even lead to new and creative solutions to the persistent problem of stigmatization. Highlights: Parents face stigmatization associated with their children's disabilities. Parents' sensitivity to stigmatization can result in social isolation. Parents weigh the risk of stigmatization against the benefit of special education. Japanese parents preferred support to be holistically and unobtrusively provided. Japanese parents' experiences sensitize Western professionals to stigmatization.